Measurement, Uncertainty, and the Dataspace - Nathan Miller (Oz, 2011)
New digital technologies are dramatically transforming our environments and behaviors. Today’s vast communication networks, comprised of over 140 quadrillion transistors, filter volumes of information at rates unimaginable just two decades ago.